Differences in the Evaluation of Prosocial Lies: A Cross-Cultural Study of Canadian, Chinese, and German Adults - Giles, Renuka M.; Rothermich, Kathrin; Pell, Marc D. (Frontiers in Communication, 2019)
In daily life, humans often tell lies to make another person feel better about themselves, or to be polite or socially appropriate in situations when telling the blunt truth would be perceived as inappropriate. Prosocial lies are a form of nonliteral communication used cross-culturally, but how they are evaluated depends on socio-moral values and communication strategies. We examined how prosocial lies are evaluated by Canadian, Chinese, and German adults. Participants watched videos and rated politeness, appropriateness, and predicted frequency of use of prosocial lies and blunt truths. A two-way intention x culture interaction was observed for appropriateness and predicted frequency of use. These results suggest that the evaluation of prosocial lies is influenced by an interplay of intercultural communication strategies depending on cultural group membership.